Penerapan Metode Human Centered Design pada Perancangan Sistem Informasi Curhat Online Berbasis Web - Astuti, Nita Fuji; Kurniasih, Tatit (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
Mental health is a very worrying health case in recent times. The number of cases that have hit the young generation of our nation is a serious threat. Pressures and challenges are often major factors in mental health crises and lack of support and places to tell stories to make a person keep everything in his mind that can hurt his mind and mentality. In this case, the research aims to overcome the problem through the implementation of a website-based online vent information system designed as a means of online vent using a Human-Centered Design approach. This Human-Centered Design approach involves a stage of user context specification, user needs, system design, and system testing using the Blackbox testing method and WebQual method. The main objective of this information system is to provide a safe and structured platform for individuals to express their feelings and emotions comfortably and safely, as well as provide support to reduce the level of mental and mental stress among the young generation of Indonesia.